Contemporary points on monitoring the spatial organization of the human body in the process of physical education - Kashuba, Vitaliy; Lopatsky, Sergiy; Rudenko, Yulia (Journal of Education, Health and Sport, 2017)
Actuality. The spatial organization of the bodies biolanceres is the most important concept consequent with the orientation of the body and its motor action in space. The monitoring of spatial organization of the human body is of much importance while improvement its motor functions under modern conditions of natural evolution, biological and social interaction. Objectives of research: To provide information about peculiarities of components influencing on monitoring of the human body spatial organization in the process of physical education. Results of research. Monitoring the spatial organization of body is the most important element of the management process. To use monitoring of the spatial organization of the body means to get, process, analyze data which represents completed temporary phase or whole cycle for further pedagogical influences. Using these data is made a comparison between the actual and projected indicators obtained as a result of the health-improving sessions, and some corrections are made in the training process. The technology of computer diagnostics of human posture using video-computer complex includes analysis of sagittal and frontal profiles (13-angle and 3-line characteristics) of human posture in relation to the somatic frame of reference. As a model of musculoskeletal system a 14-segment cinematic chain is used. Conclusions. A variety of instrumental and analytical methods for studying the state of spatial organization of the human body have been developed today. However, due to the large number of monitoring technologies for spatial organization of the human body there are currently practically no scientifically substantiated data on the use of complex monitoring technologies that allow a thorough analysis of the spatial organization of the human body in the process of physical education. The further research will be associated with the development of information and methodological system aimed on measuring the state of spatial organization of the human body in the process of physical education.